CORPORATE DECISION MAKING DALAM KOMUNIKASI ORGANISASI - Rismayanti, Rebekka (Universitas Negeri Yogyakarta, 2016)
In an organization, decision making is anessential factor to achieve its goals. The decision-making process is a process of selecting the best alternative from many alternatives that systematically chosen as a way to resolve the problem. The decision is seen as a